2021
DOI: 10.21203/rs.3.rs-941798/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Cross-Industry Universal Laws of Exponential Booking Curves

Abstract: In recent years, the e-commerce market has grown with the spread of the internet worldwide every year. Accordingly, in service industries, purchasing products with reservations has become common. With the spread of online reservations, the booking curve, which is the concept of the time series in the cumulative number of reservations and has been used for sales optimization in the airline ticket and hotel industries, has been used in various industries. Booking curves in specific industries have been studied, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…We predicted the reservation demand forecast on the usage days of each facility, where the data can be regressed in the interval t * ≤ t. Then, we used t * = 30 and the division constant N = 13. We prepared a full-year reservation data set in 2019 based on the previous study [7] and divided it into two periods. One is the first half year, that is, from January 1 to June 30, and the second is the latter half year, that is, from July 1 to December 31, 2019.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We predicted the reservation demand forecast on the usage days of each facility, where the data can be regressed in the interval t * ≤ t. Then, we used t * = 30 and the division constant N = 13. We prepared a full-year reservation data set in 2019 based on the previous study [7] and divided it into two periods. One is the first half year, that is, from January 1 to June 30, and the second is the latter half year, that is, from July 1 to December 31, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…In the service industry, it is found that the booking curve universally follows an exponential decay function [7]. Here, the booking curve represents the cumulative sum of the number of reservations toward the usage day, which is used in many industries, including hotels and rental cars.…”
Section: Application For Real Datamentioning
confidence: 99%
See 1 more Smart Citation